ILRAD 1991 annual report - International Laboratory for Research on Animal Diseases (International Laboratory for Research on Animal Diseases, 1992)
This annual report highlights ILRAD's (International Laboratory for Research on Animal Diseases) activities on theileriosis, trypanosomiasis, socio-economics, cooperative programmes - training and information, and research support. Epidemiology and biology; theileria antigens, and vaccine development are topics discussed under the chapter theileriosis while diagnosis and epidemiology; trypanosome antigens; molecular genetics; host immune responses, and genetics of host resistance are topics discussed under the chapter trypanosomiasis. The socio-economics part examines epidemiology, target populations, economic impact of disease control, nutritional impact of disease control, geographical information systems, and computer models.